Tricks

22/08/2009 - 20:12 von Christian Weiß | Report spam
Hallo NG!
Wo ist hier der Fehler?

1+1 = 1 + sqrt(1)
= 1 + sqrt((-1) * (-1))
= 1 + sqrt(-1) * sqrt(-1)
= 1 + i * i
= 1 + i²
= 1 - 1 = 0 ???


Gruß Christian
 

Lesen sie die antworten

#1 Norbert Marrek
22/08/2009 - 20:37 | Warnen spam
Christian Weiß schrieb:
Hallo NG!
Wo ist hier der Fehler?

1+1 = 1 + sqrt(1)
= 1 + sqrt((-1) * (-1))


hier sqrt(a*b) != sqrt(a)*sqrt(b) im Komplexen
= 1 + sqrt(-1) * sqrt(-1)
= 1 + i * i
= 1 + i²
= 1 - 1 = 0 ???


Gruß Christian


Ähnliche fragen